PROBLEM SEMANTIS DAN SOLUSI PEMAHAMAN MULTIKULTURALISME, INTERKULTURALISME, DAN CROSS-CULTURAL - Sokhi Huda; Moh. Ali Aziz (Jurnal Masyarakat dan Budaya, 2020)
A semantic problem arises around the terms Multiculturalism, Interculturalism, and Cross-Cultural. The first two terms are involved in intensive discussion, while the last term tends to be in the realm of praxis. Semantic problems begin with Multiculturalism as a term that has many meanings. This problem received a response in the form of multiculturalism as an approach to the clarity of its features. In the development of perspectives, a multiculturalism problem occurs when dealing with the term Interculturalism as a comparative approach. There are two perspective arguments; arguments that support Multiculturalism and responsive arguments. Discussion of the problem increases when â€œinterculturalismâ€ is used to show a specific model of â€œmanaging cultural diversityâ€ in Quebec which is articulated in explicit opposition to Canadian multiculturalism, but differs from important respect from the European interculturalism model. The two approaches contain indications of strategic advantages in the shift to the term â€œinterculturalismâ€ because the term â€œmulticulturalismâ€ is seen as being politically tarnished over the past decade. At the height of the discussion there was criticism of the flow of Multiculturalism studies which almost completely ignored the contributions of primary disciplines, especially anthropology and social psychology, especially contact theory. Finally, three points of understanding solutions can be proposed; (1) Multiculturalism is a holistic concept and an ideological basis of recognition of cultural differences, (2) Interculturalism is a model of managing cultural differences according to different regional cultural bases, (3) Cross-cultural interaction patterns, action programs, skills, and conflict management instruments.